ANALISIS PENGARUH RASIO KEUANGAN TERHADAP KINERJA BANK (Studi pada Perbankan yang Terdaftar di BEI Tahun 2010-2012) - Harish Ari Nurfahmi; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2014)
This research aims to determine the impact of the capital, asset quality, management, earning, and liquidity to performance of the bank. Capital proxied by CAR (Capital Adequacy Ratio), asset quality proxied by NPL (Non Performing Loan), management proxied by NIM (Net Interest Margin), earning proxied by BOPO and liquidity proxied by LDR (Loan to Deposit Ratio). Meanwhile the bank’s performance that proxied by using ROA (Return On Assets). This study used secondary data with the sample is banking companies listed in the Indonesia Stock Exchange (BEI) in 2010-2012. Analysis technique used is a classic assumption test covering normality test, multicolinierity test, heteroscedastisity test and autocorrelation test. Other test using multiple linear regression and hypothesis test use t-statistic to test partial regression coefficient in level of significance 5%. The results of this research shows that capital, earning and liquidity has significantly negative effects toward bank’s performance. While asset quality and management has significantly positive effects toward bank’s performance.